2016
DOI: 10.1111/jfpp.12845
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed as an Ingredient for Nutritional Improvement of Fish Jerky

Abstract: The effect of seaweed incorporation on the quality of fish jerky was studied. Sargassum wightii was incorporated in proportions of 0, 3, and 5% in Tuna jerky batter formulation. Physicochemical, microbiological, antioxidant, and sensory qualities were assessed. Total fiber content increases from 0.91 to 2.49% in seaweed incorporated sample. The additional seaweed produced samples with less tensile strength. The results showed that addition of seaweed increase the amounts of the macro minerals and trace element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Another known brown seaweed is Sargassum wightii. Hanjabam et al [191] suggested that this macroalgae could be used as a functional ingredient in ready-to-eat dried products such as tuna jerky. In addition to enriching the product with fiber, macro minerals, and trace elements, it improved antioxidant and microbial quality.…”
Section: Ros Antioxmentioning
confidence: 99%
“…Another known brown seaweed is Sargassum wightii. Hanjabam et al [191] suggested that this macroalgae could be used as a functional ingredient in ready-to-eat dried products such as tuna jerky. In addition to enriching the product with fiber, macro minerals, and trace elements, it improved antioxidant and microbial quality.…”
Section: Ros Antioxmentioning
confidence: 99%
“…Atomic absorption spectroscopy (AAS) is a very trustful methodology and highly sensible for detecting elements but is also very time consuming for routine analysis since it requires the analyses of one element at a time. This technique is being replaced by others, mainly by inductively coupled plasma optical emission spectroscopy (ICP-OES) [ 32 , 33 , 34 ] and inductively coupled plasma mass spectrometry (ICP-MS) [ 35 , 36 , 37 ]. The former allows analysis of multiple elements at a time, but, as it lacks sensitivity to detect ultra-trace elements, it is only adequate for macro-elemental analysis.…”
Section: Accumulation Of Minerals By Macroalgaementioning
confidence: 99%
“…Note that as meat is not a good source of Mg, the formulation of these seaweed-fortified meat products might represent a good strategy to improve the general intake of this microelement [ 103 ]. In the field of fish-based products, Hanjabam et al [ 33 ] showed that the incorporation of Sargassum swartzii (0–5%) into tuna jerkies resulted in a dose-dependent increase in the levels of several macro- and micro-minerals, namely K, Ca, Mg, Mn, and Fe.…”
Section: Consumption Of Macroalgaementioning
confidence: 99%
“…In parallel, the mineral fraction of seaweed has also received a lot of attention since it can reach up to 40% of seaweed’s dry weight [ 10 ]. In addition, many seaweeds show a high potassium/sodium ratio that can help to balance modern dietary habits, which are typically characterized by the intake of high and unhealthy levels of sodium [ 11 ]. Moreover, red and green macroalgae are painted as an alternative, or complement, to traditional protein sources, as levels in some seaweed species can reach up to 47%and 26% of the dry weight (dw) [ 12 ], respectively.…”
Section: Introductionmentioning
confidence: 99%